Pengelolaan Tambang Galian C terhadap Lingkungan Hidup di Kabupaten Bulukumba: Analisis Fiqh Bi’ah - Albar, Sri Aulia Almadani; Kahfi, Ashabul; Budiman, Budiman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Activities from mining excavation C (types of mining sand, soil, krikil and limestone) are increasingly soaring, the need for materials is very important to support personal development and development in an area, regency, or city. This thesis highlights the impact of mining excavation C on the environment in Balong Village, Ujungloe District, Bulukumba Regency. The damage that occurred was predominantly due to a lack of consideration and understanding related to problems arising in planning, operating and overcoming post-mining damage. The importance of the application of Fiqh Bi'ah in protecting the environment to realize the benefit of the ummah because it limits humans in taking action. This type of research is field research with normative (syar'i) and sociological approaches. The data collection methods used are observation, interviews, documentation, and reference tracing. Then data management techniques are carried out through three stages, namely: data reduction, data presentation, and conclusions. The results of this study show that the negative impacts felt by the people of Balong Village due to mining excavated C. The establishment of illegal mines that have a negative impact on the environmental ecosystem and damage the social and economic sectors. The impacts caused such as, damage to the agricultural sector of residents, damage to road access, mining exploration. To minimize environmental damage that occurs, it is important to apply the fiqh Bi'ah to realize the benefit of the people. Fiqh bi'ah provides boundaries, foundations and how to act for a Muslim in addressing environmental damage. Such as, protecting the environment is the same as maintaining religion (hifz al-din), protecting the environment is the same as (hifz al-nafs), protecting the environment is the same as guarding offspring (hifdz al-nasl), protecting the environment is the same as guarding reason (hifz al-aql), protecting the environment is the same as guarding property (hifz al-mal).